Physical Activity Levels and Recreational Participation Among Physiotherapists: A Cross-Sectional Correlational Study - Constantin Ciucurel; George Mihail Man; Marilena Monica Tantu; Mariana Ionela Tudor; Georgeta Ionescu; Ana Catalina Tantu; Elena Ioana Iconaru (Journal of Functional Morphology and Kinesiology)
Background/Objectives: Healthcare professions impose high physical and mental demands, potentially affecting health. Despite advocating for active lifestyles, many physiotherapists do not meet recommended physical activity levels (PALs). This study explores physical activity patterns and recreational engagement among practicing physiotherapists. Methods: A cross-sectional correlational design examined the relationship between physical activity and recreational participation among 60 physiotherapists (38 females, 22 males, mean age 38.62 ± 9.78 years). Data were collected using the International Physical Activity Questionnaire—Short Form (IPAQ-SF) and the Pittsburgh Enjoyable Activities Test (PEAT). The analysis focused on bivariate correlations between PAL, energy expenditure (MET), recreational habits (PEAT score), and sociodemographic and anthropometric variables. Results: The IPAQ-SF results indicated that 38.3% of participants had a low PAL, 40.0% a moderate level, and 21.7% a high level. Average energy expenditure was 1927.62 ± 1479.73 MET-minutes/week. PEAT data indicated moderate engagement in recreational activities (mean score: 22.63 ± 7.76), with participants predominantly involved in low-intensity, passive leisure. Significant positive correlations were observed between PEAT scores and both MET values (Kendall’s tau-b = 0.669, p ≤ 0.01) and PALs (Kendall’s tau-b = 0.804, p ≤ 0.01), indicating that higher engagement in recreational activities is associated with greater energy expenditure and overall physical activity levels. Conclusions: Despite the physical demands of their profession, many physiotherapists report low activity levels. The positive correlations between physical activity, energy expenditure, and recreational engagement highlight the need for structured exercise to support both personal health and professional integrity. Future research should include larger samples and objective assessments.